Transcriptional integration of the responses to iron availability in Arabidopsis by the bHLH factor ILR3. Issue 3 (25th March 2019) - Tissot, Nicolas; Robe, Kevin; Gao, Fei; Grant‐Grant, Susana; Boucherez, Jossia; Bellegarde, Fanny; Maghiaoui, Amel; Marcelin, Romain; Izquierdo, Esther; Benhamed, Moussa; Martin, Antoine; Vignols, Florence; et al.
Summary: Iron (Fe) homeostasis is crucial for all living organisms. In mammals, an integrated posttranscriptional mechanism couples the regulation of both Fe deficiency and Fe excess responses. Whether in plants an integrated control mechanism involving common players regulates responses both to deficiency and to excess is still to be determined. In this study, molecular, genetic and biochemical approaches were used to investigate transcriptional responses to both Fe deficiency and excess. A transcriptional activator of responses to Fe shortage in Arabidopsis, called bHLH105/ILR3, was found to also negatively regulate the expression of ferritin genes, which are markers of the plant's response to Fe excess. Further investigations revealed that ILR3 repressed the expression of several structural genes that function in the control of Fe homeostasis. ILR3 interacts directly with the promoter of its target genes, and repressive activity was conferred by its dimerisation with bHLH47/PYE. Last, this study highlighted that important facets of plant growth in response to Fe deficiency or excess rely on ILR3 activity. Altogether, the data presented herein support that ILR3 is at the centre of the transcriptional regulatory network that controls Fe homeostasis in Arabidopsis, in which it acts as both transcriptional activator and repressor. Abstract : See also the Commentary on this article by Kroh & Pilon, 223 : 1052–1055 .